Improving Students' Reasoning Through the Integration of Lontara Script in the Blended Learning-Mind Mapping Method - Adji Syaifullah; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Andi Srimularahmah; Vivi Elvira Ekawati; Andi ferina Herbourina Bonita (Justek : Jurnal Sains dan Teknologi, 2022)
Abstract: This study aims to determine the effectiveness of the implementation of blended learning learning methods assisted by mind mapping of Lontara script to enhance students' reasoning abilities at UPT SMP Negeri 1 Kahu,. This research is a type of quantitative descriptive research that utilizes a purposive sampling technique and a quasi-experimental nonequivalent control group design (teachers' considerations). In this study, 60 students from classes VIII B and VIII C made up the population. 30 students from class VIII B served as the experimental class in this study, whereas 30 students from class VIII C participated as the control group. The implementation of blended learning learning methods mediated by the thinking is the main emphasis of this study.The purpose of this research is to enhance student' reasoning skills through the use of blended learning techniques that are assisted by mind mapping integrated Lontara script based on android applications. The gain score test was used evaluate the study's data and determine how much the students' reasoning skills had enhanced both before and after the learning process was put into effect. The results of this study show that there is an improvement in students' reasoning abilities before and after using the blended learning method with the use of the Lontara script's mind mapping. The average result of the pretest was 47 to 79 in the posttest, with a gain score for the experimental class of 82% and a gain score of 72% for the control class.Abstrak: Penelitan ini bertujuan untuk mengetahui efektivitas penerapan metode pembelajaran blended learning berbantuan mind mapping aksara Lontara dalam meningkatkan kemampuan penalaran siswa di UPT SMP Negeri 1 Kahu. Penelitian ini merupakan jenis penelitian deskriptif kuantitatif menggunakan desain penelitian yaitu kuasi eksperimen jenis nonequivalent control group design, melalui teknik purposive sampling (pertimbangan guru). Populasi dalam penelitian ini meliputi siswa kelas VIII B dan VIII C sebanyak 60 siswa. Sampel dalam penelitian ini dibagi menjadi dua kelas, dengan 30 siswa sebagai kelas VIII B sebagai kelas eksperimen dan 30 siswa sebagai kelas VIII C sebagai kelas kontrol. Fokus penelitian ini adalah penerapan metode pembelajaran blended learning berbantuan mind mapping terintegrasi aksara Lontara berbasis aplikasi android dalam meningkatkan kemampuan penalaran siswa yang diterapkan pada kelas eksperimen. Analisis data yang digunakan pada penelitian ini adalah uji gain score untuk mengetahui seberapa besar peningkatan kemampuan penalaran siswa sebelum dan sesudah pelaksanaan proses pembelajaran. Hasil penelitian ini menunjukkan terdapat peningkatan kemampuan penalaran siswa sebelum menggunakan metode pembelajaran blended learning berbantuan mind mapping aksara lontara dan setelah menggunakan metode pembelajaran blended learning berbantuan mind mapping aksara lontara dengan hasil rata-rata pretest 47 menjadi 79 pada posttest dengan gain score untuk kelas eksperimen sebesar 82% sedangkan kelas kontrol sebesar 72%.